EFFECTS OF NONSTOICHIOMETRY AND CHEMICAL INHOMOGENEITY ON THE ORDER-DISORDER PHASE-FORMATION IN THE COMPLEX PEROVSKITE COMPOUNDS, BA(NI1/3NB2/3)O-3 AND BA(ZN1/3NB2/3)O-3 - KIM, IT; HONG, KS; YOON, SJ (CHAPMAN HALL LTD, 1995)
The order-disorder phase formation of the complex perovskite compounds, Ba(Ni1/3Nb2/3)O-3 and Ba(Zn1/3Nb2/3)O-3, was investigated by various heat treatments. Heat-treated samples were characterized using X-ray diffraction, SEM, and EDS, interactively. On the basis of lattice parameter measurements, the defect concentration in the complex perovskite compounds was thought to control ordered or disordered phase formation. The chemical inhomogeneity in the calcined powder was responsible for the formation of a liquid phase in the non-equilibrium state. These compounds are postulated to melt incongruently above temperature at which the ordered phase forms. Irrespective of extended heat treatments, second phases were observed but could not be identified by XRD due to lack of information. The second phase in BNN was unreacted NiO with a small amount of barium and niobium, and the second phase in BZN was a pyrochlore-like compound of which the composition was Ba:Nb = 1:1 with a small amount of zinc.
Keywords: CERAMICS